Comparative characteristic of criminal liability for sexual offence against juveniles under law of foreign countries and delinquency prevention - Voznyak, O.A.; Babajanyan, Y.L. (World Applied Sciences Journal 30 (10), 1376-1379, 2014)
The present article deals with comparative analysis of criminal liability for sexual offence against juveniles under the law of the Republic of Kazakhstan and some foreign countries. The article provides statistical data regarding sexual offences in respect of juveniles both in the Republic of Kazakhstan and in several foreign countries (USA, France, Switzerland, FRG and in others). The study and statistical data analysis have enabled the authors to reveal the state and causes of such crime and to identify the criminal and legal ways of fighting these crimes and some ways of their prevention.
Keywords: Corruption of minors; Criminal liability; Juvenile; Rape; Sexual aggression; Sexual intercourse; Sexual offence; Violent lecherous actions